Production method of environment-friendly polycarbonate

Through the combination of titanium silicon molecular sieve composite catalyst and pyridine ionic liquid modified hydrotalcite, the problem of insufficient decomposition and flame retardancy of polycarbonate materials at high temperatures is solved, and the high heat resistance and resistance of environmentally friendly polycarbonate is achieved It has high impact resistance at low temperatures.

CN119264632AActive Publication Date: 2025-01-07DONGGUAN YUJIE IND INVESTMENT CO LTD

Patent Information

Application Number
CN202411516015.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Existing polycarbonate materials decompose under extremely high temperature conditions, releasing harmful gases, and existing flame retardants and catalysts are not environmentally friendly, making it difficult to meet the requirements of high heat resistance and flame retardancy, and at the same time, there are high chromaticity and insufficient impact resistance. The problem.

Method used

Using titanium silicon molecular sieve composite catalyst and pyridine ionic liquid modified hydrotalcite, environmentally friendly polycarbonate is prepared through transesterification reaction and polycondensation reaction, combining rubber elastomers and compatible agents to improve the heat resistance, flame retardancy of the material and Impact resistance.

Benefits of technology

The produced polycarbonate has low color, excellent heat resistance and flame retardant, especially at low temperatures, which shows high impact resistance, meets the V0 flame retardant standard, and the environmental protection of the catalyst avoids metal ions falling off. question.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107500630000151
    Figure BDA0005107500630000151
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a production method of environment-friendly polycarbonate. The production method comprises the following steps: S1, adding diphenyl carbonate, isosorbide and bisphenol fluorene into a reaction kettle, protecting by using a nitrogen atmosphere, and then mixing to obtain a mixed material; s2, adding a titanium silicalite molecular sieve composite catalyst into the mixed material, then carrying out ester exchange reaction, then carrying out condensation polymerization, pouring out a product while the product is hot after the reaction is finished, and cooling to obtain an intermediate product; s3, mixing and stirring the intermediate product, pyridine type ionic liquid modified hydrotalcite, a rubber elastomer, a compatilizer and an antioxidant to obtain a premix; and S4, carrying out melt extrusion, strip drawing, water cooling, air drying, pelletizing and drying on the premix in a double-screw extruder to obtain the environment-friendly polycarbonate. The polycarbonate produced by the production method not only has low chromaticity, but also has excellent impact resistance, heat resistance and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a production method of environmentally friendly polycarbonate. Background Art

[0002] Polycarbonate (PC) is a high molecular polymer containing carbonate groups in its molecular chain, which has excellent comprehensive properties. The application areas of polycarbonate include: (1) Building materials: used to produce fire-resistant doors, windows, partitions and other building components to improve the safety of buildings; (2) Electronic equipment: used to manufacture fire-resistant components of electronic products such as computer casings and mobile phone cases to protect internal components from fire damage; (3) Transportation: used in automobile interior parts, ship parts, etc. to improve the overall safety performance of transportation; (4) Safety equipment: used to manufacture safety equipment such as protective glasses and masks to provide flame and heat protection.

[0003] Polycarbonate itself has good heat resistance, but under extremely high temperature conditions, if it exceeds its heat resistance range, it may still decompose and release harmful gases. As the requirements for polymer materials increase, higher requirements are also placed on the heat resistance of polycarbonate; polycarbonate itself has a certain flame retardant effect, and its flame retardant grade can reach V-2 level, which is a self-extinguishing engineering plastic. This means that under certain conditions, polycarbonate materials can extinguish themselves during the combustion process, thereby slowing the spread of the fire. In order to meet higher flame retardant standards, such as achieving V-0 flame retardancy, flame retardants are usually added to further improve the flame retardant properties of polycarbonate. These flame retardants mainly include phosphates, silicones and sulfonates. Although these flame retardants can improve the flame retardancy of polycarbonate products to a certain extent, these flame retardants are not very environmentally friendly during use. In addition, in existing studies, PC is often blended with other polymers with good toughness (such as polyamide, i.e., nylon) to increase the toughness of polycarbonate products, but the addition of these polymers has the defect of high toughness and low strength, and cannot effectively increase the impact resistance of polycarbonate materials. In the process of preparing polycarbonate, catalysts play a vital role. At present, the main catalysts are organic tin compounds, zinc salts, and titanium salts. These metal compound catalysts will not be removed during the preparation of polycarbonate, and metal ions will also partially fall off and exist in polycarbonate, which is not only environmentally friendly, but also makes the color of polycarbonate high.

[0004] Therefore, there is an urgent need for a method for producing environmentally friendly polycarbonate, and the polycarbonate produced has the characteristics of heat resistance, impact resistance, flame retardancy 94V0, etc., and has good mechanical properties within the generally used temperature range. Summary of the invention

[0005] The purpose of the present invention is to provide a method for producing an environmentally friendly polycarbonate, wherein the raw materials used in the method are all environmentally friendly raw materials, and the polycarbonate produced by the production method not only has low chroma, but also has excellent impact resistance, heat resistance and flame retardancy.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for producing an environmentally friendly polycarbonate, the method comprising:

[0008] S1: adding diphenyl carbonate, isosorbide and bisphenol fluorene into a reaction kettle, protecting with nitrogen atmosphere, and then mixing to obtain a mixture;

[0009] S2: adding a titanium silicon molecular sieve composite catalyst to the mixed material to carry out an ester exchange reaction, followed by a polycondensation reaction, and after the reaction is completed, pouring out the product while hot, and cooling to obtain an intermediate product;

[0010] S3: mixing and stirring the intermediate product, the pyridine-type ionic liquid-modified hydrotalcite, the rubber elastomer, the compatibilizer and the antioxidant to obtain a premix;

[0011] S4 melt-extrudes the premix in a twin-screw extruder, draws strands, water-cools, air-dries, pelletizes, and dries to obtain an environmentally friendly polycarbonate.

[0012] Furthermore, the molar ratio of diphenyl carbonate, isosorbide and bisphenol fluorene is 1:(0.5-0.7):(0.3-0.4), preferably 1:0.6:0.4.

[0013] Furthermore, in step S1, the mixing conditions include: firstly melting the reactants at 120-160°C, and then stirring at 120-160°C at a rotation speed of 500-600 rpm for 5-20 minutes.

[0014] Furthermore, the weight of the titanium silicon molecular sieve composite catalyst is 0.01-0.04% of the weight of diphenyl carbonate.

[0015] Furthermore, the transesterification conditions include: temperature of 180-190° C., pressure of 35-45 kPa, and time of 1-2 hours.

[0016] Furthermore, the conditions of the polycondensation reaction include: raising the temperature to 280-300° C., starting the vacuum pump to evacuate the reactor to a pressure of 70-80 Pa, and reacting for 1-2 hours.

[0017] The catalysts used in the prior art are generally metal-type catalysts, but metal-type catalysts have the defect of metal leaching that harms the ecological environment, and after the reaction, metal ions generally exist in the polymer, which will cause defects such as poor color of the polymer. The alkaline molecular sieve composite catalyst in the present invention refers to a catalyst with an alkaline molecular sieve as the main body. The catalyst titanium silicon molecular sieve composite catalyst of the present invention has excellent stability, its metal will not fall off, and has excellent environmental protection, and can also avoid other performance defects caused by the shedding of metal ions.

[0018] Furthermore, the preparation method of the titanium silicon molecular sieve composite catalyst comprises:

[0019] (1) dispersing titanium silicalite in ethanol to obtain a suspension, then adding 3-mercaptopropyltrimethoxysilane to react, and after the reaction is completed, cooling the system to room temperature to obtain a material containing mercapto-modified titanium silicalite;

[0020] (2) Adding 1-allyl-3-methylimidazole hexafluorophosphate and azobisisobutyronitrile to a material containing mercapto-modified titanium silicalite and mixing at room temperature to obtain a mixture, then charging the mixture into a high-pressure reactor to initiate a reaction, and after the reaction is completed, the system is cooled to room temperature and centrifuged to obtain a solid precipitate, the solid precipitate is washed with water, and then dried to obtain a titanium silicalite composite catalyst.

[0021] Furthermore, in step (1), the dispersion conditions include: dispersing under ultrasonic conditions for 20-30 minutes.

[0022] Furthermore, in step (1), the reaction conditions include: reacting at 50-60°C for 0.5-1 hour, and then reflux reacting at 80-90°C for 5-7 hours.

[0023] Furthermore, in step (1), the number of washing times with ethanol is 3-6 times.

[0024] Furthermore, the silicon-titanium molar ratio of the titanium silicon molecular sieve is 30-70.

[0025] Furthermore, the average particle size of the titanium silicate molecular sieve is 0.2-10 microns.

[0026] The titanium silicon molecular sieve in the present invention can be obtained commercially, and the titanium silicon molecular sieve is purchased from Aos Catalytic Materials (Dalian) Co., Ltd.

[0027] Furthermore, in step (1): the weight ratio of the titanium silicalite to ethanol is 1:(100-200).

[0028] Furthermore, in step (1): the weight ratio of the titanium silicalite to 3-mercaptopropyltrimethoxysilane is 1:(10-20).

[0029] Furthermore, the weight ratio of the titanium silicalite molecular sieve to 1-allyl-3-methylimidazolium hexafluorophosphate is 1:(0.1-1), preferably 1:(0.3-0.4).

[0030] Furthermore, the weight ratio of the titanium silicon molecular sieve to azobisisobutyronitrile is 1:(0.01-0.1), preferably 1:(0.05-0.06).

[0031] Furthermore, in step (2), the conditions for initiating the reaction include: reacting at 95-120° C. for 15-20 hours.

[0032] Furthermore, in step (2), the drying conditions include: a temperature of 70-80° C., a vacuum degree of 0.07-0.09 MPa, and a drying time of 8-20 hours.

[0033] Furthermore, in step (2), the number of water washings is 3-5 times.

[0034] Although a single titanium silicalite molecular sieve can also be used to prepare polycarbonate resin, the inventors have found that the heat resistance of the prepared polycarbonate resin is poor. However, the titanium silicalite molecular sieve composite catalyst modified with 1-allyl-3-methylimidazole hexafluorophosphate in the present invention can not only synthesize polycarbonate resin, but also prepare polycarbonate resin with good heat resistance. This may be because the titanium silicalite molecular sieve composite catalyst in the present invention can better regulate the distribution of polymer molecules during the preparation process to obtain a polycarbonate resin with a narrow molecular weight distribution, so that it has better heat resistance.

[0035] Existing flame retardants generally use bromine-based, nitrogen-based and red phosphorus flame retardants, which are not environmentally friendly when used. The inventors of the present invention have found that using pyridine-type ionic liquid to modify hydrotalcite can not only have excellent environmental protection, but also achieve better flame retardant effects compared to traditional flame retardants.

[0036] Furthermore, the preparation method of the pyridine ionic liquid modified hydrotalcite comprises: dispersing the hydrotalcite in anhydrous ethanol, then adding the pyridine ionic liquid and stirring, then dropping a silane coupling agent to react, continuing the reaction for 30-40 minutes after the dropwise addition is completed, then filtering, and solid phase drying to obtain the pyridine ionic liquid modified hydrotalcite.

[0037] In the present invention, adding pyridine ionic liquid to modify hydrotalcite can not only better increase the flame retardancy of polycarbonate, but also better increase the impact resistance of polycarbonate. This may be because a part of the pyridine ionic liquid is connected to the hydrotalcite through a coupling agent, and the pyridine ionic liquid makes it possible for a part to be connected to the interlayer hydroxyl groups of the hydrotalcite through hydrogen bonds. When flame retardant, the hydrotalcite can release structural water and interlayer anions, and these released substances can effectively reduce combustion gases. At this time, the hydrogen bonds and π-π stacking structures in the pyridine ionic liquid interact with the specific structure of the hydrotalcite to further increase the stability and heat resistance of the molecules in the system, and have more excellent high-temperature flame retardancy.

[0038] Furthermore, the average particle size of the hydrotalcite is 0.1-2 microns, preferably 0.5-1 microns.

[0039] The magnesium aluminum hydrotalcite in the present invention can be obtained from commercial sources, such as magnesium aluminum hydrotalcite purchased from Kaisima (Dandong) High-tech Materials Technology Co., Ltd., and its average particle size is 0.6 microns.

[0040] Furthermore, the pyridine-type ionic liquid is selected from brominated N-C2-C10 alkylpyridine, preferably brominated N-C4-C8 alkylpyridine, and examples of brominated N-C4-C8 alkylpyridine include brominated N-butylpyridine, brominated N-hexylpyridine, brominated N-octylpyridine, and the like.

[0041] The study further found that the pyridine ionic liquid modified hydrotalcite prepared by using brominated N-C4-C8 alkylpyridine can better increase the impact resistance of polycarbonate, especially the low-temperature impact resistance. This may be because the pyridine ionic liquid modified hydrotalcite has a lamellar structure, which can better play a toughening role. The pyridine ionic liquid can act as a plasticizer, especially at low temperatures. The long chain structure in brominated N-C4-C8 alkylpyridine can hinder the freezing of the molecular chain, so that the polycarbonate has better low-temperature impact toughness.

[0042] Furthermore, the coupling agent is selected from at least one of KH550, KH550, KH560, KH580, KH590, KH602 and KH792.

[0043] Furthermore, the weight ratio of the hydrotalcite to anhydrous ethanol is 1:(20-40).

[0044] Furthermore, the weight ratio of the hydrotalcite to the pyridinium ionic liquid is 1:(0.2-1), preferably 1:(0.3-0.4).

[0045] Furthermore, the weight ratio of the hydrotalcite to the silane coupling agent is 1:(0.05-0.1), preferably 1:(0.03-0.04).

[0046] Furthermore, when preparing the pyridine type ionic liquid modified hydrotalcite, the silane coupling agent is added dropwise within 30-40 minutes. Those skilled in the art can control the dropping rate according to the dropping time, and the present invention will not elaborate on this.

[0047] Furthermore, when preparing the pyridine type ionic liquid modified hydrotalcite, the reaction conditions include: the temperature is 40-45°C,

[0048] Furthermore, when preparing the pyridine type ionic liquid modified hydrotalcite, the drying conditions include: temperature of 50-60° C., vacuum degree of 0.07-0.09 MPa, and time of 5-10 hours.

[0049] Furthermore, the rubber elastomer is selected from SEBS elastomer.

[0050] When rubber elastomer is used alone to increase the toughness of polycarbonate, there is often a disadvantage of "high toughness and low strength", which is not particularly advantageous for increasing the impact strength of the final polycarbonate. The synergistic effect of the rubber elastomer and the pyridine ionic liquid modified hydrotalcite in the present invention can achieve the advantages of high strength and toughness, thereby better increasing the impact resistance of polycarbonate.

[0051] Furthermore, the melt index of the SEBS elastomer at 230° C. and 5.0 kg is 2-8 g / 10 min, preferably 4-6 g / 10 min.

[0052] The SEBS elastomer in the present invention can be obtained from commercial sources, and is preferably SEBS G1652 from Kraton, USA, which has a melt index of 5 g / 10 min at 230° C. and 5.0 kg.

[0053] Furthermore, the compatibilizer is selected from styrene grafted maleic anhydride and / or polystyrene grafted glycidyl methacrylate, preferably styrene grafted maleic anhydride.

[0054] The compatibilizer in the present invention can be obtained from the market, for example, styrene grafted maleic anhydride is styrene grafted maleic anhydride produced by Cray Valley, model number SMA1000P.

[0055] Furthermore, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 2246, antioxidant 264, antioxidant 300, antioxidant 442, antioxidant BHT and antioxidant DSTP.

[0056] Furthermore, the weight ratio of the intermediate product to the pyridine-type ionic liquid-modified hydrotalcite is 100:(25-30).

[0057] Furthermore, the weight ratio of the intermediate product to the rubber elastic body is 100:(10-15).

[0058] Furthermore, the weight ratio of the intermediate product to the compatibilizer is 100:(1-3).

[0059] Furthermore, the weight ratio of the intermediate product to the antioxidant is 100:(0.1-0.3).

[0060] Furthermore, in step S3, the mixing and stirring conditions include: a stirring speed of 1200-2000 rpm and a time of 5-10 minutes.

[0061] Further, in step S4, the conditions for melt extrusion include: the temperature control of zones 1 to 8 of the twin-screw extruder is: zone 1 temperature 260-280°C, zone 2 temperature 270-290°C, zone 3 temperature 270-290°C, zone 4 temperature 280-300°C, zone 5 temperature 280-300°C, zone 6 temperature 280-300°C, zone 7 temperature 280-300°C and zone 8 temperature 280-300°C; the screw speed is 300-400rpm.

[0062] Furthermore, in step S4, the conditions for melt extrusion include: the temperature control of zones 1 to 8 of the twin-screw extruder is: zone 1 temperature 270°C, zone 2 temperature 275°C, zone 3 temperature 275°C, zone 4 temperature 285°C, zone 5 temperature 290°C, zone 6 temperature 290°C, zone 7 temperature 290°C and zone 8 temperature 290°C; the screw speed is 300-400rpm.

[0063] The strip drawing, water cooling, air drying, pelletizing and drying in step S4 of the present invention are conventional technical means in the art and will not be elaborated in detail in the present invention.

[0064] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0065] The polycarbonate produced by the production method of the present invention has low chromaticity and impact resistance, especially low-temperature impact resistance, and also has excellent flame retardancy and heat resistance. It is speculated that this is because the titanium silicon molecular sieve composite catalyst of the present invention can prepare a polycarbonate intermediate product with a narrow molecular weight distribution, and the pyridine ionic liquid modified hydrotalcite, rubber elastomer and polycarbonate intermediate product work together to achieve toughening, strengthening and heat resistance effects. DETAILED DESCRIPTION

[0066] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] Example 1

[0068] The present embodiment provides a method for producing an environmentally friendly polycarbonate, the method comprising: S1, adding diphenyl carbonate, isosorbide and bisphenol fluorene to a reaction kettle, using a nitrogen atmosphere for protection, and then mixing to obtain a mixed material; S2, adding a titanium silicon molecular sieve composite catalyst to the mixed material, performing an ester exchange reaction, and then performing a polycondensation reaction, pouring out the product while hot after the reaction is completed, and cooling to obtain an intermediate product; S3, mixing and stirring the intermediate product, pyridine ionic liquid modified hydrotalcite, rubber elastomer, compatibilizer and antioxidant to obtain a premix; S4, melt-extruding the premix in a twin-screw extruder, pulling strips, water cooling, air drying, pelletizing, and drying to obtain an environmentally friendly polycarbonate;

[0069] The molar ratio of diphenyl carbonate, isosorbide and bisphenol fluorene is 1:0.6:0.4;

[0070] In step S1, the mixing conditions include: firstly melting the reactants at 150°C, and then stirring at 150°C at a rotation speed of 500 rpm for 10 minutes;

[0071] The weight of the titanium silicon molecular sieve composite catalyst is 0.02% of the weight of diphenyl carbonate;

[0072] The transesterification conditions include: temperature of 190°C, pressure of 40 kPa, and time of 1.5 hours;

[0073] The conditions for the polycondensation reaction include: raising the temperature to 290°C, starting the vacuum pump to evacuate the reactor to a pressure of 70 Pa, and reacting for 1.5 hours;

[0074] The preparation method of a titanium silicon molecular sieve composite catalyst comprises: (1) dispersing a titanium silicon molecular sieve in ethanol to obtain a suspension, then adding 3-mercaptopropyltrimethoxysilane to react, and after the reaction is completed, cooling the system to room temperature to obtain a material containing a mercapto-modified titanium silicon molecular sieve; (2) adding 1-allyl-3-methylimidazole hexafluorophosphate and azobisisobutyronitrile to the material containing the mercapto-modified titanium silicon molecular sieve and mixing at room temperature to obtain a mixed material, then charging the mixed material into a high-pressure reactor to initiate a reaction, and after the reaction is completed, cooling the system to room temperature, centrifuging to obtain a solid phase precipitate, washing the solid phase precipitate with water, and then drying to obtain a titanium silicon molecular sieve composite catalyst;

[0075] In step (1): the dispersion conditions include: dispersion under ultrasonic conditions for 25 minutes;

[0076] In step (1), the reaction conditions include: reacting at 55°C for 1 hour, and then reflux reacting at 85°C for 6 hours;

[0077] In step (1): the number of ethanol washings is 5 times;

[0078] The silicon-titanium molar ratio of the titanium silicate molecular sieve is 46; the average particle size of the titanium silicate molecular sieve is 1 micron, and it is purchased from Aos Catalytic Materials (Dalian) Co., Ltd.;

[0079] In step (1): the weight ratio of the titanium silicalite to ethanol is 1:150;

[0080] In step (1): the weight ratio of the titanium silicalite to 3-mercaptopropyltrimethoxysilane is 1:15;

[0081] The weight ratio of titanium silicalite to 1-allyl-3-methylimidazolium hexafluorophosphate is 1:0.35;

[0082] The weight ratio of titanium silicalite molecular sieve to azobisisobutyronitrile is 1:0.05;

[0083] In step (2): the conditions for initiating the reaction include: reacting at 100° C. for 18 hours;

[0084] In step (2), the drying conditions include: temperature of 75° C., vacuum degree of 0.08 MPa, and drying time of 12 hours;

[0085] In step (2): the number of water washings is 4 times;

[0086] The preparation method of pyridine type ionic liquid modified hydrotalcite comprises: dispersing hydrotalcite in anhydrous ethanol, then adding pyridine type ionic liquid and stirring, then dropping silane coupling agent to react, continuing to react for 35 minutes after the dropwise addition is completed, then filtering, and solid phase drying to obtain pyridine type ionic liquid modified hydrotalcite;

[0087] The hydrotalcite was purchased from the magnesium-aluminum hydrotalcite of Kaisima (Dandong) High-tech Materials Technology Co., Ltd., and its average particle size was 0.6 μm;

[0088] The pyridine type ionic liquid is selected from N-octylpyridinium bromide; the coupling agent is selected from KH550; the weight ratio of the hydrotalcite to anhydrous ethanol is 1:30; the weight ratio of the hydrotalcite to the pyridine type ionic liquid is 1:0.35; the weight ratio of the hydrotalcite to the silane coupling agent is 1:0.04;

[0089] When preparing pyridine-type ionic liquid-modified hydrotalcite, the silane coupling agent is added dropwise within 35 minutes; when preparing pyridine-type ionic liquid-modified hydrotalcite, the reaction conditions include: temperature of 45°C; when preparing pyridine-type ionic liquid-modified hydrotalcite, the drying conditions include: temperature of 50°C, vacuum degree of 0.07MPa, and time of 6 hours.

[0090] The rubber elastomer is selected from SEBS elastomer; the SEBS elastomer is SEBS G1652 of Kraton, USA, and its melt index is 5g / 10min under the conditions of 230°C and 5.0kg;

[0091] The compatibilizer is styrene grafted maleic anhydride of Crayville, model number SMA1000P.

[0092] The antioxidant is selected from antioxidant 1010;

[0093] The weight ratio of the intermediate product to the pyridine ionic liquid modified hydrotalcite is 100:28; the weight ratio of the intermediate product to the rubber elastomer is 100:12; the weight ratio of the intermediate product to the compatibilizer is 100:2; the weight ratio of the intermediate product to the antioxidant is 100:0.2; in step S3, the mixing and stirring conditions include: the stirring speed is 1500rpm, and the time is 8 minutes; in step S4, the melt extrusion conditions include: the temperature control of zones 1 to 8 of the twin-screw extruder is: zone 1 temperature 270°C, zone 2 temperature 275°C, zone 3 temperature 275°C, zone 4 temperature 285°C, zone 5 temperature 290°C, zone 6 temperature 290°C, zone 7 temperature 290°C and zone 8 temperature 290°C; the screw speed is 320rpm.

[0094] Example 2

[0095] The present embodiment provides a method for producing an environmentally friendly polycarbonate, the method comprising: S1, adding diphenyl carbonate, isosorbide and bisphenol fluorene to a reaction kettle, using a nitrogen atmosphere for protection, and then mixing to obtain a mixed material; S2, adding a titanium silicon molecular sieve composite catalyst to the mixed material, performing an ester exchange reaction, and then performing a polycondensation reaction, pouring out the product while hot after the reaction is completed, and cooling to obtain an intermediate product; S3, mixing and stirring the intermediate product, pyridine ionic liquid modified hydrotalcite, rubber elastomer, compatibilizer and antioxidant to obtain a premix; S4, melt-extruding the premix in a twin-screw extruder, pulling strips, water cooling, air drying, pelletizing, and drying to obtain an environmentally friendly polycarbonate;

[0096] The molar ratio of diphenyl carbonate, isosorbide and bisphenol fluorene is 1:0.5:0.5;

[0097] In step S1, the mixing conditions include: firstly melting the reactants at 140°C, and then stirring at 140°C at a rotation speed of 500 rpm for 10 minutes;

[0098] The weight of the titanium silicon molecular sieve composite catalyst is 0.01% of the weight of diphenyl carbonate;

[0099] The transesterification conditions include: temperature of 185°C, pressure of 38 kPa, and time of 2 hours;

[0100] The conditions for the polycondensation reaction include: raising the temperature to 285°C, starting the vacuum pump to evacuate the reactor to a pressure of 70 Pa, and reacting for 1.5 hours;

[0101] The preparation method of a titanium silicon molecular sieve composite catalyst comprises: (1) dispersing a titanium silicon molecular sieve in ethanol to obtain a suspension, then adding 3-mercaptopropyltrimethoxysilane to react, and after the reaction is completed, cooling the system to room temperature to obtain a material containing a mercapto-modified titanium silicon molecular sieve; (2) adding 1-allyl-3-methylimidazole hexafluorophosphate and azobisisobutyronitrile to the material containing the mercapto-modified titanium silicon molecular sieve and mixing at room temperature to obtain a mixed material, then charging the mixed material into a high-pressure reactor to initiate a reaction, and after the reaction is completed, cooling the system to room temperature, centrifuging to obtain a solid phase precipitate, washing the solid phase precipitate with water, and then drying to obtain a titanium silicon molecular sieve composite catalyst;

[0102] In step (1): the dispersion conditions include: dispersion under ultrasonic conditions for 25 minutes;

[0103] In step (1), the reaction conditions include: reacting at 55°C for 1 hour, and then reflux reacting at 90°C for 6 hours;

[0104] In step (1): the number of ethanol washings is 5 times;

[0105] The silicon-titanium molar ratio of the titanium silicate molecular sieve is 46; the average particle size of the titanium silicate molecular sieve is 1 micron, and it is purchased from Aos Catalytic Materials (Dalian) Co., Ltd.;

[0106] In step (1), the weight ratio of the titanium silicalite to ethanol is 1:200;

[0107] In step (1): the weight ratio of the titanium silicalite to 3-mercaptopropyltrimethoxysilane is 1:10;

[0108] The weight ratio of titanium silicalite to 1-allyl-3-methylimidazolium hexafluorophosphate is 1:0.3;

[0109] The weight ratio of titanium silicalite molecular sieve to azobisisobutyronitrile is 1:0.05;

[0110] In step (2): the conditions for initiating the reaction include: reacting at 100° C. for 18 hours;

[0111] In step (2), the drying conditions include: temperature of 75° C., vacuum degree of 0.08 MPa, and drying time of 12 hours;

[0112] In step (2): the number of water washings is 4 times;

[0113] The preparation method of pyridine type ionic liquid modified hydrotalcite comprises: dispersing hydrotalcite in anhydrous ethanol, then adding pyridine type ionic liquid and stirring, then dropping silane coupling agent to react, continuing to react for 35 minutes after the dropwise addition is completed, then filtering, and solid phase drying to obtain pyridine type ionic liquid modified hydrotalcite;

[0114] The hydrotalcite was purchased from the magnesium-aluminum hydrotalcite of Kaisima (Dandong) High-tech Materials Technology Co., Ltd., and its average particle size was 0.6 μm;

[0115] The pyridine type ionic liquid is selected from N-octylpyridinium bromide; the coupling agent is selected from KH550; the weight ratio of the hydrotalcite to anhydrous ethanol is 1:40; the weight ratio of the hydrotalcite to the pyridine type ionic liquid is 1:0.4; the weight ratio of the hydrotalcite to the silane coupling agent is 1:0.05;

[0116] When preparing pyridine-type ionic liquid-modified hydrotalcite, the silane coupling agent is added dropwise within 35 minutes; when preparing pyridine-type ionic liquid-modified hydrotalcite, the reaction conditions include: temperature of 45°C; when preparing pyridine-type ionic liquid-modified hydrotalcite, the drying conditions include: temperature of 50°C, vacuum degree of 0.07MPa, and time of 6 hours.

[0117] The rubber elastomer is selected from SEBS elastomer; the SEBS elastomer is SEBS G1652 of Kraton, USA, and its melt index is 5g / 10min under the conditions of 230°C and 5.0kg;

[0118] The compatibilizer is styrene grafted maleic anhydride of Crayville, model number SMA1000P.

[0119] The antioxidant is selected from antioxidant 1010;

[0120] The weight ratio of the intermediate product to the pyridine ionic liquid modified hydrotalcite is 100:20; the weight ratio of the intermediate product to the rubber elastomer is 100:20; the weight ratio of the intermediate product to the compatibilizer is 100:2; the weight ratio of the intermediate product to the antioxidant is 100:0.2; in step S3, the mixing and stirring conditions include: the stirring speed is 1500rpm, and the time is 8 minutes; in step S4, the melt extrusion conditions include: the temperature control of zones 1 to 8 of the twin-screw extruder is: zone 1 temperature 270°C, zone 2 temperature 275°C, zone 3 temperature 275°C, zone 4 temperature 285°C, zone 5 temperature 290°C, zone 6 temperature 290°C, zone 7 temperature 290°C and zone 8 temperature 290°C; the screw speed is 320rpm.

[0121] Comparative Example 1

[0122] The difference between this comparative example and Example 1 is:

[0123] The titanium silicate molecular sieve composite catalyst was replaced with titanium silicate molecular sieve, and the silicon-titanium molar ratio of the titanium silicate molecular sieve was 46; the average particle size of the titanium silicate molecular sieve was 1 micron, and it was purchased from Aos Catalytic Materials (Dalian) Co., Ltd.

[0124] Comparative Example 2

[0125] The difference between this comparative example and Example 1 is:

[0126] The pyridine-type ionic liquid-modified hydrotalcite was replaced by hydrotalcite, and the hydrotalcite was purchased from the magnesium-aluminum hydrotalcite of Kaisima (Dandong) High-tech Materials Technology Co., Ltd., and its average particle size was 0.6 μm.

[0127] Comparative Example 3

[0128] The difference between this comparative example and Example 1 is:

[0129] The pyridine-type ionic liquid-modified hydrotalcite was replaced by N-octylpyridinium bromide.

[0130] Comparative Example 4

[0131] The difference between this comparative example and Example 1 is:

[0132] The pyridinium-type ionic liquid is selected from N-ethylpyridinium bromide.

[0133] Comparative Example 5

[0134] The difference between this comparative example and Example 1 is:

[0135] During the preparation, no pyridine-type ionic liquid-modified hydrotalcite is added.

[0136] Comparative Example 6

[0137] The difference between this comparative example and Example 1 is:

[0138] No rubber elastomer is added during preparation.

[0139] Performance Testing

[0140] 1. Chroma test: Use the American HunterLab colorimeter to measure the b value;

[0141] 2. After conditioning the polycarbonate at -50°C for 5 hours, test the cantilever beam impact strength according to ASTM D256 with a test thickness of 3.2 mm;

[0142] 3. Test the flame retardancy of polycarbonate according to UL-94 standard

[0143] 4. Heat deformation temperature test: The test was conducted in accordance with ASTM D648 standard, with a load weight of 1.82 MPa, a heating rate of 120°C / h, and a test thickness of 3.2 mm.

[0144] The test results are shown in Table 1.

[0145] Table 1 Performance test results

[0146]

[0147] It can be seen from the above performance test results that the polycarbonate in Examples 1-2 has lower chromaticity and impact resistance, especially low-temperature impact resistance, and also has excellent flame retardancy and heat resistance. In particular, the comprehensive performance of Example 1 is the most outstanding. It is speculated that this is because the titanium silicon molecular sieve composite catalyst in the present invention can prepare a polycarbonate intermediate product with a narrow molecular weight distribution, and at the same time, the pyridine ionic liquid modified hydrotalcite, rubber elastomer and polycarbonate intermediate product work together to achieve the effects of toughening, strengthening and heat resistance.

[0148] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. The catalyst in comparative example 1 uses a single titanium silicon molecular sieve, and the heat resistance of the final polycarbonate is significantly reduced, indicating that the titanium silicon molecular sieve composite catalyst in the present invention can better increase the heat resistance of polycarbonate; in comparative example 2, the pyridine ionic liquid modified hydrotalcite is replaced with a single hydrotalcite, and the low-temperature toughness and flame retardancy of the polycarbonate are significantly reduced, further indicating that the pyridine ionic liquid modified hydrotalcite can better increase the low-temperature impact and flame retardancy of polycarbonate; in comparative example 3, the pyridine ionic liquid modified hydrotalcite is replaced with a pyridine ionic liquid, and the low-temperature toughness and flame retardancy of the polycarbonate are significantly reduced, further indicating that the pyridine ionic liquid modified hydrotalcite can better increase the low-temperature impact and flame retardancy of polycarbonate. It shows that the hydrotalcite modified by pyridine ionic liquid can better increase the low-temperature impact and flame retardancy of polycarbonate; in comparative example 4, the pyridine ionic liquid is N-ethylpyridine, and the low-temperature impact of polycarbonate is reduced to a certain extent, indicating that the selection of a specific pyridine ionic liquid in the present invention can better increase the low-temperature impact of polycarbonate; the low-temperature impact and heat resistance of the polycarbonate without pyridine ionic liquid modified hydrotalcite in comparative example 5 and without rubber elastomer in comparative example 6 are both reduced, indicating that the pyridine ionic liquid modified hydrotalcite needs to be selected in the present invention to cooperate with the rubber elastomer to increase the comprehensive performance of polycarbonate

[0149] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for producing an environmentally friendly polycarbonate, characterized in that: The production method comprises: S1: adding diphenyl carbonate, isosorbide and bisphenol fluorene into a reaction kettle, protecting with nitrogen atmosphere, and then mixing to obtain a mixture; S2: adding a titanium silicon molecular sieve composite catalyst to the mixed material to carry out an ester exchange reaction, followed by a polycondensation reaction, and after the reaction is completed, pouring out the product while hot, and cooling to obtain an intermediate product; S3: mixing and stirring the intermediate product, the pyridine-type ionic liquid-modified hydrotalcite, the rubber elastomer, the compatibilizer and the antioxidant to obtain a premix; S4 melt-extrudes the premix in a twin-screw extruder, draws strands, water-cools, air-dries, pelletizes, and dries to obtain an environmentally friendly polycarbonate.

2. The production method according to claim 1, characterized in that The molar ratio of diphenyl carbonate, isosorbide and bisphenol fluorene is 1:(0.5-0.7):(0.3-0.4); in step S1, the mixing conditions include: first melting the reactants at 120-160° C., and then stirring at 120-160° C. at a speed of 500-600 rpm for 5-20 minutes; The weight of the titanium silicon molecular sieve composite catalyst is 0.01-0.04% of the weight of diphenyl carbonate; The transesterification conditions include: temperature of 180-190°C, pressure of 35-45 kPa, and time of 1-2 hours; The conditions of the polycondensation reaction include: raising the temperature to 280-300° C., starting the vacuum pump to evacuate the reactor to a pressure of 70-80 Pa, and reacting for 1-2 hours.

3. The production method according to claim 1, characterized in that The preparation method of the titanium silicon molecular sieve composite catalyst comprises: (1) dispersing titanium silicalite in ethanol to obtain a suspension, then adding 3-mercaptopropyltrimethoxysilane to react, and after the reaction is completed, cooling the system to room temperature to obtain a material containing mercapto-modified titanium silicalite; (2) Adding 1-allyl-3-methylimidazole hexafluorophosphate and azobisisobutyronitrile to a material containing mercapto-modified titanium silicalite and mixing at room temperature to obtain a mixture, then charging the mixture into a high-pressure reactor to initiate a reaction, and after the reaction is completed, the system is cooled to room temperature and centrifuged to obtain a solid precipitate, the solid precipitate is washed with water, and then dried to obtain a titanium silicalite composite catalyst.

4. The production method according to claim 3, characterized in that: In step (1), the dispersion conditions include: dispersion under ultrasonic conditions for 20-30 minutes; the reaction conditions include: reaction at 50-60° C. for 0.5-1 hour, followed by reflux reaction at 80-90° C. for 5-7 hours; and the number of ethanol washings is 3-6 times.

5. The production method according to claim 3, characterized in that: The silicon-titanium molar ratio of the titanium silicalite is 30-70:1; the average particle size of the titanium silicalite is 0.2-10 microns; the weight ratio of the titanium silicalite to ethanol is 1:(100-200); the weight ratio of the titanium silicalite to 3-mercaptopropyltrimethoxysilane is 1:(10-20); the weight ratio of the titanium silicalite to 1-allyl-3-methylimidazole hexafluorophosphate is 1:(0.1-1); the weight ratio of the titanium silicalite to azobisisobutyronitrile is 1:(0.01-0.1).

6. The production method according to claim 3, characterized in that: In step (2), the conditions for initiating the reaction include: reacting at 95-120° C. for 15-20 hours; the conditions for drying include: temperature of 70-80° C., vacuum degree of 0.07-0.09 MPa, time of 8-20 hours; and the number of water washings is 3-5 times.

7. The production method according to claim 1, characterized in that: The preparation method of the pyridine ionic liquid modified hydrotalcite comprises: dispersing the hydrotalcite in anhydrous ethanol, then adding the pyridine ionic liquid and stirring, then dropping a silane coupling agent to react, continuing the reaction for 30-40 minutes after the dropwise addition is completed, then filtering, and solid phase drying to obtain the pyridine ionic liquid modified hydrotalcite.

8. The production method according to claim 7, characterized in that: The average particle size of the hydrotalcite is 0.1-2 microns; the pyridine type ionic liquid is selected from brominated N-C2-C10 alkylpyridine; the coupling agent is selected from at least one of KH550, KH550, KH560, KH580, KH590, KH602 and KH792; the weight ratio of the hydrotalcite to anhydrous ethanol is 1:(20-40); the weight ratio of the hydrotalcite to the pyridine type ionic liquid is 1:(0.2-1); the weight ratio of the hydrotalcite to the silane coupling agent is 1:(0.05-0.1); the reaction conditions include: the temperature is 40-45°C.

9. The production method according to claim 1, characterized in that: The rubber elastomer is selected from SEBS elastomer; the compatibilizer is selected from styrene grafted maleic anhydride and / or polystyrene grafted glycidyl methacrylate; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 2246, antioxidant 264, antioxidant 300, antioxidant 442, antioxidant BHT and antioxidant DSTP; the weight ratio of the intermediate product to pyridine ionic liquid modified hydrotalcite is 100:(25-30); the weight ratio of the intermediate product to the rubber elastomer is 100:(10-15); the weight ratio of the intermediate product to the compatibilizer is 100:(1-3); the weight ratio of the intermediate product to the antioxidant is 100:(0.1-0.3).

10. The production method according to any one of claims 1 to 9, characterized in that: In step S3, the mixing and stirring conditions include: a stirring speed of 1200-2000rpm, and a time of 5-10 minutes; in step S4, the melt extrusion conditions include: the temperature control of zones 1 to 8 of the twin-screw extruder is: zone 1 temperature 260-280°C, zone 2 temperature 270-290°C, zone 3 temperature 270-290°C, zone 4 temperature 280-300°C, zone 5 temperature 280-300°C, zone 6 temperature 280-300°C, zone 7 temperature 280-300°C and zone 8 temperature 280-300°C; the screw speed is 300-400rpm.

Citation Information

Patent Citations

  • Load type non-metallocene catalyst and preparation thereof

    CN101412767A

  • Starch-based thermoplastic composite material

    CN102443194A

  • Method for synthesizing cyclic carbonate ester in micro reactor system

    CN102464521A

  • Fluorescent and flame retarded functionalization hydrotalcite and preparation method thereof

    CN103059341A

  • Titanium silicalite molecular sieve, preparation method thereof and phenol hydroxylation method

    CN116332194A

Cited By

  • Polyethylene composite hose and preparation method thereof

    CN120363550A

  • Filtration and adsorption activated carbon composite material as well as preparation method and application thereof

    CN122298358A